2018
DOI: 10.3892/ol.2018.9163
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced plasma miR‑26a‑5p promotes the progression of bladder cancer via targeting PTEN

Abstract: The current study aimed to evaluate the expression and specific role of miR-26a-5p in the progression of bladder cancer (BC). Reverse transcription-quantitative polymerase chain reaction analysis was performed to evaluate the level of miR-26a-5p in BC cancer and healthy controls. The present data showed that plasma miR-26a-5p was significantly increased in BC patients. Furthermore, BC tissues exhibited greater levels of miR-26a-5p compared with adjacent non-neoplastic tissues-26a-5p. Compared with BC patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Significantly growth inhibition was found in estrogen stimulated tumor xenograft models and ER+ breast cancer cells when up-regulating miR-26a expression [30]. Moreover, some researches demonstrated miR-26a-5p may also indirectly promote initiation and progression of some cancers [20,31,32]. Up-regulated expression of miR-26a was observed in gastric cancer cells MKN-28 and promoted cells proliferation, migration and invasion [32].…”
Section: Discussionmentioning
confidence: 99%
“…Significantly growth inhibition was found in estrogen stimulated tumor xenograft models and ER+ breast cancer cells when up-regulating miR-26a expression [30]. Moreover, some researches demonstrated miR-26a-5p may also indirectly promote initiation and progression of some cancers [20,31,32]. Up-regulated expression of miR-26a was observed in gastric cancer cells MKN-28 and promoted cells proliferation, migration and invasion [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, downregulation of PTEN by miR-26a-5p have been reported to promote the progression of bladder cancer. 27 29 Therefore, we propose that miR-26a-5p exhibits its effects not only through the regulation of FAF1 expression, but also by other means.…”
Section: Discussionmentioning
confidence: 99%
“…9(c), samples with low expression are at greater risk of survival (HR=0.602, 95% CI =0.407 to 0.891). In fact, in previous studies, the two microRNAs have been reported to be tumor suppressor microRNAs that often suppress bladder cancer development by inhibiting expression of some oncogenes [35]- [37]. We also analyzed the GO and KEGG enrichment of mRNAs in MRM 4.…”
Section: E the Prognostic Signatures Of Mrmsmentioning
confidence: 99%